In What Ways Do Educators Respond to Plagiarism Among Students? - Pelila, John Rey Osben; Desalit, Johnell Bringas; Soliba, Bernadette Lamsis (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Plagiarism is prevalent, and it's no surprise that students engage in intellectual dishonesty. While suspension may be the corresponding punishment for misconduct in some student codes, teachers often show tolerance by considering various approaches before taking further action. Therefore, this study aimed to identify teachers' strategies for addressing student plagiarism. We employed a quasi-experimental design, specifically a posttest-only nonequivalent group design. The study's treatment group consisted of three students who plagiarized their work in one of their subjects. In the intervention phase, we conducted a discourse session and created a yes-no diagram to assess the students. Later, we held a student consultation, allowing them to redo their activity and write a reflection paper after indicating their willingness. We checked the resubmitted outputs and monitored and observed all students in their subsequent activities throughout the semester to identify any signs of plagiarism. The study found that the intervention, which allowed students to resubmit their work after discussing plagiarism issues with them, proved beneficial. Despite time constraints and a potential lack of expertise in certain areas, students demonstrated accountability by avoiding plagiarism in their resubmitted work, as reflected in their feedback. Additionally, post-intervention monitoring showed a decrease in instances of plagiarism. Therefore, we concluded that while punitive measures like suspension exist, it's crucial to consider the circumstances and offer opportunities for redemption before imposing severe consequences.